STRATEGI PROMOSI KUB UMA PALAK LESTARI DALAM MENARIK WISATAWAN DI DESA PEGUYANGAN DENPASAR UTARA - Endrayani, Endrayani; Titing Koerniawaty, Francisca; Darsana, I Made (Berajah Journal, 2024)
The aim of this research is to identify the target audience, analyze message design, select media, and design promotional strategies for KUB Uma Palak Lestari to attract tourists in Peguyangan Village, North Denpasar. A qualitative descriptive approach and SWOT analysis are used to develop strategies in the aspects of destination, management, institution, and marketing. The results of the study indicate that the target audience of Uma Palak Lestari consists of individuals or groups, aged 1-80 years, both male and female. The message design uses easily understandable sentences. The media used include online platforms such as Facebook and Instagram, as well as offline media such as banners along the streets of Peguyangan Village. Uma Palak Lestari's promotional strategy encompasses a combination of outdoor and electronic media, personal selling through guides, innovative sales promotions, a public relations team focusing on publicity, and direct marketing via telephone and direct interaction between guides and visitors.